Dampak Gerakan Literasi Sekolah Pada Minat Baca Siswa SD di Kabupaten Sumba Barat Daya - Daga, Agustinus Tanggu; Engge, Yohanes; Tanggela, Kristoforus (Paedagogie, 2025)
The School Literacy Movement (SLM ) has been implemented in Southwest Sumba Regency (SSR) since 2018 to improve students' reading culture. This study analyzes the impact of SLM on students' reading interest. This quantitative research uses a survey method. This study involved 97 elementary school students as a random sample whose number was determined using the Slovin formula. Data collection used a questionnaire. Prerequisite tests showed that the data were normally distributed, but did not meet the linearity assumption. The analysis was continued with the Spearman test. The results showed that the SLM score reached 72.39 and the reading interest score was 61.00, both of which are included in the high category. The research data showed a normal distribution but was not homogeneous. Spearman's Rank analysis yielded a significance value of 0.000 < 0.05, indicating that SLM has a positive and significant effect on the reading interest of elementary school students in SSR. This finding indicates the need to strengthen the implementation of SLM aspects to increase effectiveness in building sustainable student reading interest.